BUSINESS COMMUNICATION STRATEGY IN IMPROVING SERVICE QUALITY AT THE PUTRI SHOP OF THE AL-MASHDUQIAH ISLAMIC BOARDING SCHOOL - Fithri, Naylal; Firda Amelia Putri; Nur Iftah Maufida; Robiyatul Adawiyah; Roiqotul Fitria; Shevina Nazalia Rachmadini (IZZI: Jurnal Ekonomi Islam, 2025)
Toko Putri at Pondok Pesantren Al-Mashduqiah serves as a provider of necessities for students and the surrounding community. In an era of increasingly fierce competition, service quality has become a key factor in attracting and retaining customers. This journal uses a literature review method to analyze various business communication strategies that can be applied to improve service quality at Toko Putri, referencing literature published after 2020. This study aims to analyze the business communication strategies implemented at Putri Store in Al-Mashduqiah Islamic Boarding School to improve service quality. Effective communication is key to attracting and retaining customers. Employee training in communication skills has proven to enhance the ability to provide friendly and responsive service. The implementation of a feedback system also provides valuable insights for management to make continuous improvements in the services provided. By implementing the right communication strategies, Toko Putri has successfully increased customer satisfaction and built strong loyalty. This study is expected to contribute to the development of business communication strategies in the retail sector, particularly in the boarding school environment. Additionally, the results of this study can serve as a reference for other stores seeking to improve service quality through effective communication.